Defisiensi Zat Besi dengan Kejadian Anemia pada Ibu Hamil - Mardliyataini Haji Sulaiman; Rostika Flora; Mohammad Zulkarnain; Indah Yuliana; Risnawati Tanjung (Journal of Telenursing (JOTING), 2022)
This study aims to analyze iron deficiency on the incidence of anemia in pregnant women in the Kepahiang district in 2021. The method used is descriptive-analytic with a cross-sectional design. The research sample was 100 pregnant women in the second and third trimesters who were taken randomly from 14 working areas of the Public Health Center in Kepahiang Regency. The data obtained were analyzed using the chi-square test. The results showed that the number of pregnant women with abnormal iron deficiency experienced anemia as much as 97.8% and pregnant women with normal iron deficiency experienced anemia as much as 77.8%. The statistical test results obtained a p-value of 0.008 and a PR of 12.857. In conclusion, there is a significant relationship between iron deficiency and the incidence of anemia in pregnant women in Kepahiang Regency in 2021. Keywords: Anemia, Iron Deficiency, Pregnant Women